Exploring the effects of journal article features: Implications for automated prediction of scholarly impact - Abramo Giovanni; D’Angelo Ciriaco Andrea; Grilli Leonardo (Journal of Data and Information Science)
Scholars face an unprecedented ever increasing demand for acting as reviewers for journals, recruitment and promotion committees, granting agencies, and research assessment agencies. Consequently, journal editors face an ever increasing scarcity of experts willing to act as reviewers. It is not infrequent that reviews diverge, which forces editors to recur to additional reviewers or make a final decision on their own. The purpose of the proposed bibliometric system is to support of editors’ accept/reject decisions in such situations.